2017
DOI: 10.1111/gcb.13683
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional abundance shifts among North American birds and the relative influence of multifaceted climate factors

Abstract: Shifts in species distributions are major fingerprint of climate change. Examining changes in species abundance structures at a continental scale enables robust evaluation of climate change influences, but few studies have conducted these evaluations due to limited data and methodological constraints. In this study, we estimate temporal changes in abundance from North American Breeding Bird Survey data at the scale of physiographic strata to examine the relative influence of different components of climatic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 75 publications
3
40
0
Order By: Relevance
“…Westward shifts were common; 37.6% of the species had significant westward longitude shifts in their breeding COA. Our results are consistent with two recent analyses of North American birds that also found high occurrences of avian abundances shifting west during the breeding season (Currie & Venne, ; Huang et al, ). Additionally, Fei et al () examined 86 tree species across the eastern United States and most commonly observed westward range shifts over the course of 30 years.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Westward shifts were common; 37.6% of the species had significant westward longitude shifts in their breeding COA. Our results are consistent with two recent analyses of North American birds that also found high occurrences of avian abundances shifting west during the breeding season (Currie & Venne, ; Huang et al, ). Additionally, Fei et al () examined 86 tree species across the eastern United States and most commonly observed westward range shifts over the course of 30 years.…”
Section: Discussionsupporting
confidence: 93%
“…Recent literature emphasizes species‐specific multidirectional shifts in distributions (Currie & Venne, ; Fei et al, ; Gillings, Balmer, & Fuller, ; Huang et al, ; VanDerWal et al, ). Complex interactions between temperature and precipitation are driving species‐specific responses to changes in climate (Garcia, Cabeza, Rahbek, & Araújo, ; Tingley, Koo, Moritz, Rush, & Beissinger, ; Tingley et al, ; VanDerWal et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results highlight that distributional responses to global change are highly variable, and that southward shifts are a possible strategy for coping with change, despite a lack of hypotheses in the literature predicting southward shifts. Our results that 55% of centroid shifts were northward and 44% of shifts were southward are similar to other multispecies studies of distribution shifts (Zuckerberg et al , Currie and Venne , Huang et al ). We did not find strong predictors of southward shifts in breeding distribution centroid, similar to other studies that have shown southward shifts in distributions without clear evidence of an effect of life history (Zuckerberg et al ).…”
Section: Discussionsupporting
confidence: 92%